Synthesis, Characterization and Antifungal Screening of Ni(II), Cu(II) and Co(II) Complexes with Nitrogen and Oxygen Containing Schiff Base - Rai, B.K.; Kumari, Rachana (Asian Journal of Chemistry, 2011)
[M(L)2X2], where M = Co(II), Ni(II) and Cu(II); L = 2-ethylindole-3-carboxaldehydesemicarbazone [EICS], X = Cl-, Br-, I- and NO3- have been synthesized. The ligand and its metal complexes have been characterized by elemental analyses, molar mass, IR, UV, molar conductance and magnetic susceptibility measurements. Octahedral structure has been proposed on the basis of above physicochemical and spectroscopic measurements. These complexes have been screened for their antifungal effect on Aspergillus flavus and Salmonella typhi. All the complexes of Co(II), Ni(II) and Cu(II) have been shown good activity as antifungal agents on some selected fungal strains.